Exploration of Prognostic Biomarkers for Lung Adenocarcinoma Through Bioinformatics Analysis - Tu, Zhengliang; He, Xiangfeng; Zeng, Liping; Meng, Di; Zhuang, Runzhou; Zhao, Jiangang; Dai, Wanrong (Frontiers in Genetics, 2021)
With the development of computer technology, screening cancer biomarkers based on public databases has become a common research method. Here, an 8-gene prognostic model, which could be used to judge the prognosis of patients with lung adenocarcinoma (LUAD), was developed through bioinformatics methods. This study firstly used several gene datasets from GEO database to mine differentially expressed genes (DEGs) in LUAD tissue and healthy tissue via joint analysis. Later, enrichment analysis for the DEGs was performed, and it was found that the DEGs were mainly activated in pathways involved in extracellular matrix, cell adhesion, and leukocyte migration. Afterwards, a TCGA cohort was used to perform univariate Cox, LASSO, and multivariate Cox regression analyses for the DEGs, and a prognostic model consisting of 8 genes (GPX3, TCN1, ASPM, PCP4, CAV2, S100P, COL1A1, and SPOK2) was established. Receiver operation characteristic (ROC) curve was then used to substantiate the diagnostic efficacy of the prognostic model. The survival significance of signature genes was verified through the GEPIA database, and the results exhibited that the risk coefficients of the eight genes were basically congruous with the effects of these genes on the prognosis in the GEPIA database, which suggested that the results were accurate. Finally, combined with clinical characteristics of patients, the diagnostic independence of the prognostic model was further validated through univariate and multivariate regression, and the results indicated that the model had independent prognostic value. The overall finding of the study manifested that the 8-gene prognostic model is closely related to the prognosis of LUAD patients, and can be used as an independent prognostic indicator. Additionally, the prognostic model in this study can help doctors make a better diagnosis in treatment and ultimately benefit LUAD patients.